Resistance to tetracycline and β-lactams and distribution of resistance markers in enteric microorganisms and pseudomonads isolated from the oral cavity - Marcelle Marie Buso Ramos; Ellen Cristina Gartti-Jardim; Elerson Gaetti-Jardim Junior (University of São Paulo, 2009)
This study evaluated the occurrence of enteric bacteria and pseudomonads resistant to tetracycline and β-lactams in the oral cavity of patients exhibiting gingivitis (n=89), periodontitis (n=79), periodontally healthy (n=50) and wearing complete dentures (n=41). Microbial identification and presence of resistance markers associated with the production of β-lactamases and tetracycline resistance were performed by using biochemical tests and PCR. Susceptibility tests were carried out in 201 isolates of enteric cocci and rods. Resistance to ampicillin, amoxicillin/clavulanic acid, imipenem, meropenem and tetracycline was detected in 57.4%, 34.6%, 2.4%, 1.9% and 36.5% of the isolates, respectively. β-lactamase production was observed in 41.2% of tested microorganisms, while the most commonly found β-lactamase genetic determinant was gene blaTEM. Tetracycline resistance was disseminated and a wide scope of tet genes were detected in all studied microbial genus.